2010
DOI: 10.2478/s11534-009-0095-8
|View full text |Cite
|
Sign up to set email alerts
|

Plasma treatment studies of MIS devices

Abstract: Abstract:Silicon nitride films have emerged as the possible future dielectrics for ultra large scale integration (ULSI). Because the interface state density of silicon nitride/silicon interface in metal insulator semiconductor (MIS) configuration is more than an order of magnitude larger than that of silicon dioxide/silicon interface, plasma treatment studies on silicon nitride films have been undertaken for the possible improvement. Accordingly, silicon nitride films of various composition have been prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…The observed results have two possible explanations. (i) Reports have had shown that plasma had been used to improve silicon nitride properties or used to clean the Au surface from particles [28, 29]. In our case, plasma could help to improve the quality of the line by cleaning off native oxide or amorphous carbon.…”
Section: Resultsmentioning
confidence: 88%
“…The observed results have two possible explanations. (i) Reports have had shown that plasma had been used to improve silicon nitride properties or used to clean the Au surface from particles [28, 29]. In our case, plasma could help to improve the quality of the line by cleaning off native oxide or amorphous carbon.…”
Section: Resultsmentioning
confidence: 88%